Caracterización de las Propiedades Fisicoquímicas y Térmicas de Almidón de Yuca (Manihot esculenta) - Jara Ponce, Jorge Américo (2017)
Cassava is highly tolerant to harsh climatic conditions and has high productivity on marginal lands. The supply of cassava starch, is the main component of the root, is therefore sustainable and cheap. Evaluations of the physicochemical properties of cassava starch were carried out (variety: Rosada, Origin: Ayacucho - Peru). The content of amylose was 19.55 ± 1.97, the moisture content of 12.27 ± 0.77, ash of 0.19 ± 0.01 and proteins of 0.10 ± 0.10. The gelatinization temperatures were 57.66 ± 0.04 for To, 63.23 ± 0.02 for Tp and 70.96 ± 0.16 for Tc. The granular form was circular truncated, with an average granule size of 16 μm. The FT-IR spectrum shows the major groups of alcohols and carbon-oxygen-hydrogen bonds corresponding to the presence of starch. Cassava starch can be used in products that require average processing temperatures, and can be included in food systems such as thickeners, stabilizers and gelling agents in refrigerated and frozen foods.